Architectural Katas, October - December 2020 - Ford, Neal (O'Reilly Media, Inc., 2020)
About Architectural Katas : What could be better than practicing software architecture with your handpicked dream team of architects? Participants in Architectural Katas, moderated by Neal Ford, work together virtually in small groups of their choosing to solve a challenge an actual organization is facing. Everyone gets the chance to practice their craft with a real software architecture problem in a safe and social environment, and the finalists and winners earn well-deserved bragging rights (not to mention an intriguing line on their re sume). Plus a selected organization working for social good will have some of its gnarliest software architecture problems solved. How it works : You put together a first-rate team of three to five people, ready to tackle an architecture challenge. We ll share the architecture problem with you at the kickoff on October 20. Then your team will have to solve it, working virtually in whatever way is best for you (video calls, group chat, shared docs, etc.). Teams will submit their solutions by November 3 and reconvene at the semifinals on November 17 to find out which will move on to the finals on December 3. At the finals, one member of each team will present their solutions to the judges and a winner will be announced. Registration opens October 20 following the first event; the first 100 teams to sign up will be selected to participate . Not ready to compete but want to be part of the action? Register for the event and join us to see how Architectural Katas work, cast your vote for the winning team, and learn how to successfully present architecture plans to stakeholders. Series schedule: Event 1: Kickoff - October 20, 2020 Meet the judges, hear all the details on how Architectural Katas work, learn more about the software architecture problem you ll be solving, and get the chance to ask Neal any questions you may have. New Materials: Transcript Event 2: Semifinals and Architectural Presentation - November 17, 2020 Get a master class on presentation skills and learn how to successfully showcase software architecture plans to developers and stakeholders (and judges). You ll also find out the top five teams that will present in the final event. Event 3: Finals - December 3, 2020 The top five teams present their plans with Q & A, judges provide feedback, attendees vote for their favorite, and judges announce the winner. With today s registration, you ll be automatically signed up for all events in the Architectura ...